An Analysis of Translation Methods in the Children’s Story 'Jack and the Beanstalk' - Marlina Angeline (JALILA: Journal of Applied Linguistics and Literary Analysis, 2025)
This academic paper examines the translation techniques applied in the Indonesian translation of the children’s fairy tale “Jack and the Beanstalk” (A.O.V.P., 1876). The primary objective of this study is to analyze the translation methods employed by the translator in bridging cultural differences embedded in the fairy tale. This research adopts a descriptive qualitative approach, with conclusions drawn after a systematic analysis of the collected data. Primary data were obtained through textual analysis of the translated version of the story. The findings indicate that the translation of “Jack and the Beanstalk” employs various translation techniques, including word-for-word translation, free translation, idiomatic translation, literal translation, adaptation, and transference/borrowing. In addition, reduction, modulation, and amplification techniques are also identified in several parts of the text. The results suggest that the applied translation techniques produce a translation that is easily comprehensible for target-language readers, particularly children as the primary audience. Appropriate selection of translation techniques enables effective transfer of meaning from the source language into the target language. In literary translation practice, a deep understanding of cultural context is essential in order to produce translations that are acceptable and meaningful to target readers. The application of appropriate translation methods and strategies contributes to translations that are accurate, natural, and reader-oriented. This study may serve as a reference for future analyses of translation techniques in adapted fairy tales translated from foreign languages into Indonesian, particularly those involving distinct cultural backgrounds and literary nuances.